Rizobios aislados de leguminosas forrajeras de un ecosistema ganadero árido de Holguín, Cuba. Tolerancia a estrés abiótico y producción de catalasa (Fase II) - Bécquer, C. J.; Galdo, Yaldreisy; Mirabal, Analeidis; Quintana, Maribel; Puentes, Adelaida (Cuban Journal of Agricultural Science, 2017)
The objective of this research was to evaluate the tolerance to stressing abiotic factors of 11 isolated rhizobia from forage legumes (Desmodium cannum, D. triflorum and Centrosema virginianum) located in an arid ecosystem in Holguín, Cuba, and to qualitatively assess the catalase production of this isolates. The different levels of temperature, pH and NaCl were the stressing factors evaluated. Cultures were performed in solid and liquid mannitol-yeast medium, and the visible growth in the medium was considered as an evaluative criterion. All isolates grew at 34 and 35 ºC, but none at 38 ºC or 40 ºC. Except two isolates (C. virginianum and D. triflorum), the rest grew at pH 4, and 9 of them at pH 10. All isolates grew in 0.4 % NaCl, but only one (D. triflorum) grew in 1.2 %. There was no growth in 2.4 % NaCl. All isolates reacted positively to H2O2. It was concluded that there were isolates tolerant to different stressing abiotic factors, as well as with catalase production. In addition, there were isolates that, independently of the macrosymbionts from which they originated and of the morpho-cultural group to which they were circumscribed, showed tolerance to different abiotic factors, such as acidity and alkalinity, high salt concentrations and growth at 35 ºC. All this gives them potential for future application in agricultural practice under adverse environmental conditions. Inoculation tests of grasses and legumes under stressing environmental conditions are recommended to select the isolates with the highest positive effect on these cultures. Key words: forage legumes, Bradyrhizobium, abiotic stress, catalase